2016
DOI: 10.1051/0004-6361/201628833
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of radius inflation in stars approaching the slow-rotator sequence

Abstract: Context. Average stellar radii in open clusters can be estimated from rotation periods and projected rotational velocities under the assumption that the spin axis has a random orientation. These estimates are independent of distance, interstellar absorption, and models, but their validity can be limited by lacking data (truncation) or data that only represent upper or lower limits (censoring). Aims. We present a new statistical analysis method to estimate average stellar radii in the presence of censoring and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Although a correlation between rotation and radius inflation has been reported for both the Pleiades (Somers & Stassun 2017) and M35 (Jeffries et al 2021), there is a lot of scatter and it is much weaker than that between rotation and the lithium abundance, and uncertainties on empirical radii are generally relatively large (e.g. Rebull et al 2004;Lanzafame et al 2017;Jackson et al 2019). Jeffries et al (2021) also found a correlation between radius inflation and Li below about 4800 K, providing support for the idea that these structural changes are an important mechanism.…”
Section: Introductionmentioning
confidence: 89%
“…Although a correlation between rotation and radius inflation has been reported for both the Pleiades (Somers & Stassun 2017) and M35 (Jeffries et al 2021), there is a lot of scatter and it is much weaker than that between rotation and the lithium abundance, and uncertainties on empirical radii are generally relatively large (e.g. Rebull et al 2004;Lanzafame et al 2017;Jackson et al 2019). Jeffries et al (2021) also found a correlation between radius inflation and Li below about 4800 K, providing support for the idea that these structural changes are an important mechanism.…”
Section: Introductionmentioning
confidence: 89%
“…A maximum likelihood method is used to determine the average radius ratio or over-radius, ρ = R/Rm of the measured data relative to BHAC15 model radii, as a function of luminosity. The approach is similar to that used by Lanzafame et al (2017) 2). Diamonds with error bars show r sin i for targets with a relative uncertainty 30 per cent.…”
Section: Maximum Likelihood Methodsmentioning
confidence: 99%
“…2012), and with respect to a 5 Gyr solar-metallicity isochrone from BHAC15. The green point shows a previously reported measurement of ρ for Pleiades stars of 0.6 < M/M ⊙ < 0.8 and periods in the transition between the C and I gyrochronological sequences defined by Barnes (2007) (P > 2d, see Table 2 of Lanzafame et al 2017).…”
Section: ρmentioning
confidence: 96%
See 1 more Smart Citation
“…Jackson & Jeffries 2010) and observational biases are understood, then a set of R sin i estimates can be modelled to determine the true average radius for a group of stars. This technique has been used to claim the detection of inflated radii in the young K-and M-type stars of several young clusters, notably the Pleiades at an age of ≃ 120 Myr (Jackson, Jeffries & Maxted 2009;Hartman et al 2010;Jackson & Jeffries 2014a;Jackson et al 2016;Lanzafame et al 2017). In Jackson et al (2018, hereafter Paper I), we obtained the largest ever set of homogeneously determined values of v sin i and P for low-mass stars in the Pleiades to investigate radius inflation as a function of mass using Eqn.…”
Section: Introductionmentioning
confidence: 99%